Cellular and molecular pathobiology of cardiovascular disease - Homeister, Jonathon W.; Stone, James R.; Willis, Monte S. (Amsterdam ; Boston : Elsevier, AP, Academic Press is an imprint of Elsevier, 2014)
Focuses on the pathophysiology of common cardiovascular disease in the context of its underlying mechanisms and molecular biology. This book has been developed from the editors' experiences teaching an advanced cardiovascular pathology course for PhD trainees in the biomedical sciences, and trainees in cardiology, pathology, public health, and veterinary medicine.--
Includes bibliographical references and index
1 13
Keywords: Cardiovascular system -- Diseases -- Molecular aspects